The Role of Assurance in Sustainability Reports: A Systematic Literature Review - Dinarjito, Agung (Journal of Governance, Taxation and Auditing, 2026)
The increasing focus on environmental, social, and governance (ESG) matters is compelling firms to deliver clear and reliable sustainability reports. In this context, the auditing or assurance of sustainability reports is essential for enhancing the credibility of non-financial information presented to stakeholders. This study seeks to thoroughly investigate the role and advantages of sustainability report assurance utilizing a PRISMA-based Systematic Literature Review (SLR) methodology. This analysis examined 19 esteemed scientific articles published in Scopus-indexed international journals from 2016 to 2026. The summary results demonstrate that sustainability report assurance has transitioned from a merely symbolic volunteer practice to a more institutionalized corporate governance tool. Assurance enhances the quality, authenticity, and dependability of sustainability reports, thereby bolstering stakeholder trust and corporate accountability. Moreover, assurance confers internal advantages to organizations by enhancing reporting systems, controlling sustainable data, and strengthening sustainability governance. This study enhances the sustainability assurance literature and offers practical implications for corporations, regulators, and assurance providers to foster more credible and responsible sustainability reporting practices.